Local Diagnostic Reference Levels for Paediatric Head CT Procedures - Gricienė, Birutė; Šiukšterytė, Monika (Acta medica Lituanica, 2021)
Background. Patients, especially children, are exposed to substantially high doses of ionising radiation during computed tomography (CT) procedures. Children are several times more susceptible to ionising radiation than adults. Diagnostic reference levels (DRLs) are an important tool for monitoring and optimising patient radiation exposure from radiological procedures. The aim of this study is to estimate the ionising radiation exposure doses and set local DRLs for head CT examinations according to age and to compare local DRLs with national and European DRLs and with literature data in other countries.Materials and methods. Scan parameters of single-phase head CT examinations were collected. Patients were grouped by age in the following intervals:
Keywords: paediatric; computed tomography; diagnostic reference levels; patient exposure; ionising radiation